Jurisdiction Overview Implementation of Rights Transfer to Land & Building Registration with Selling-Buying Deed - Wahyu Baskoro; Bambang Tri Bawono (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purposes of this study are to: 1) Analyze the implementation of the registration of the transfer of rights to land and or buildings with a Sale and Purchase Deed at the Surakarta City Land Office. 2) Analyzing obstacles and solutions in the implementation of the registration of the transfer of rights to land and or buildings with a Sale and Purchase Deed at the Surakarta City Land Office. This research is a normative juridical approach, with descriptive analysis research specifications. Primary and secondary data collection was obtained by interview and literature study. The results of the research are: 1) The registration of the transfer of land and building rights with the Sale and Purchase Deed at the Surakarta City Land Office begins with the stage of implementing the sale and purchase transaction between the seller and the buyer. After that the sale and purchase transaction must be made a deed of sale and purchase by the PPAT, then by the PPAT it is brought to the Land Office to be registered as a certificate of ownership for the new land title holder. After the registration process, the next step is to wait for data verification from the Land Office for the issuance of certificates. 2). The obstacle in implementing the registration of the transfer of rights to land and or buildings with a Sale and Purchase Deed at the Surakarta City Land Office is that there are still many low levels of education resulting in a lack of public legal awareness, the length of the SOP for the Transfer of Name Certificates whose proof of ownership is still in the form of a Sub-district Register C (Letter C), and the lack of counseling provided to the community regarding the importance of registering the transfer of land rights due to buying and selling, and land certificates. 3). The solution to overcome obstacles in implementing the registration of the transfer of land and or building rights with the Sale and Purchase Deed at the Surakarta City Land Office is to provide or publish brochures about the importance of registering the transfer of land rights due to buying and selling, conducting counseling, improving human resources through courses/training and fixing the administration of the organization.